Melalui Pendekatan Saintifik Model Pembelajaran Covid-19 Metode Daring untuk Meningkatkan Hasil Belajar Peserta Didik Mata Pelajaran PPKn Materi Makna, Kedudukan dan Fungsi UUD Tahun 1945 di Kelas VIII.5 SMP Negeri 6 Payakumbuh Semester Ganjil Tahun Pelaj - Yulia sari (Journal on Education, 2022)
The purpose of this study was to describe the use of the online method of the Covid-19 learning model to improve student learning outcomes in PPKn subjects in class VIII.5 SMP Negeri 6 Payakumbuh. This type of research is Classroom Action Research. The research was carried out based on classroom action research steps with two cycles starting from the planning, implementation, observation and reflection stages. Research data in the form of test results, Covid-19 learning observations, field notes, and documentation of each learning improvement action. The source of research data is the process of learning activities. The data were obtained from the research subjects, namely teachers and class students, totaling 22 people, which was held from July to September 2021. The results of the analysis of research data showed that the use of the online method of the Covid-19 learning model could improve student learning outcomes. This is evident from the acquisition of learning outcomes in the aspect of knowledge which has increased, namely 64.31 in pre-cycle activities, increasing to 70.00 in the first cycle, increasing to 76.81 in the second cycle with an increase of 12.50. The learning outcomes of the skills aspect obtained an average of 62.72 in the pre-cycle, increasing to 70.00 in the first cycle and increasing to 75.90 in the second cycle with an increase of 13.18. Based on the results of this study, the conclusions of the study using the online method of Covid-19 learning models need to be applied and developed in order to improve the quality of education